Foregrounding invisible foundations: (eco-)feminist perspectives on provisioning systems - Corinna Dengler; Christina Plank (Sustainability: Science, Practice, & Policy)
Debates on provisioning systems have become more widespread in recent years. Most of these discussions, however, have centered on the monetized economy. While they have elaborated on actors and institutions in the monetized economy, they tend to ignore the foundational role of unpaid provisioning processes. This article contributes to provisioning systems scholarship by foregrounding this indispensable yet invisibilized foundation of production, distribution, and consumption. In doing so, we combine different approaches on provisioning systems in social ecology, political ecology, and political economy with chronologically older feminist economics debates on social provisioning to arrive at an ecofeminist political economy conceptualization of social-ecological provisioning. We elaborate on this conceptualization by drawing upon the example of food provisioning, thereby showing that people provision for themselves, their families, and their communities through closely interlinked paid and unpaid provisioning practices. Only by acknowledging the central role of actors and institutions in the non-monetized economy and by taking an intersectional approach to the questions of who provides and who is provided for can a more holistic picture of food provisioning be drawn. In the last part of the article, we discuss ecofeminist strategies that strengthen non-monetized social-ecological provisioning without monetizing it, thereby questioning the arbitrariness of what is (un-/under-)paid in capitalist economies.